Customer Loyalty of Islamic Banks - Adi, Pramono Hari (AFEBI Islamic Finance and Economic Review, 2016)
The highly rapid growth of sharia commercial banks have required them to compete in obtaining and retaining customers. Therefore, it is important to look carefully at the position of their brands within the industry. Among the measures to see how strong the position of a brand in the market is the level of customersâ brand loyalty. There are five levels of brand loyalty, each of which indicates particular marketing challenge to be addressed. Those levels - from least loyal to most loyal - include switcher, habitual buyer, satisfied buyer, liking the brand, and committed buyer. Using questionnaire to collect primary data from 100 respondents, the results indicate that the highest brand loyalty to Islamic banks has been at the level of satisfied buyer and liking the brand, indicating that consumer loyalty to the Islamic banks has not been perfect. Loyalty needs to be improved towards the committed buyer.Keywords: Brand, Customer Loyalty, Islamic Bank